The office complete Christmas collection [videorecording (DVD)] - Schur, Michael, 1975-; Novak, B. J., 1979-; Lieberstein, Paul; Kaling, Mindy; Carell, Steve, 1962-; Wilson, Rainn, 1966-; Krasinski, John, 1979- (Universal, 2023)
Come join Dunder Mifflin for a holiday celebration like no other with The Office: Complete Christmas Collection! Developed by Primetime Emmy Award winner Greg Daniels, relive all 7 of the wackiest workplace holiday episodes in TV history. Featuring "Christmas Party", "A Benihana Christmas", "Moroccan Christmas", "Secret Santa", "Classy Christmas", "Christmas Wishes" and "Dwight Christmas", 'tis the season for non-stop laughs.